Copper‐Catalyzed β‐Iodovinylation of Carbamates: Expedient Access to Highly Functionalized Vinyl‐Carbamates. Issue 17 (7th May 2018) - Ricard, Simon; Gagnon, Alexandre; Daoust, Benoit
Abstract: A general and efficient method for the synthesis of β‐iodovinyl carbamates via copper‐catalyzed β‐iodovinylation of acyclic carbamates is described. This method uses readily available ( E )‐1, 2‐vinyl diiodides and regioselectively affords the corresponding β‐iodovinyl carbamates in good yields with complete stereocontrol of the alkene. Further functionalization of these versatile products leads to a wide diversity of β‐functionalized vinyl‐carbamates in good to excellent yields. Abstract : Copper‐catalyzed β‐iodovinylation of acyclic carbamates using ( E )‐1, 2‐vinyl diiodides afforded the corresponding β‐iodovinyl carbamates in good yields with complete regio‐ and stereocontrol of the olefin. Further functionalization led to a wide diversity of β‐functionalized vinyl‐carbamates in good to excellent yields.